Mediating and moderating role of financial signaling, information asymmetries of corporate governance in debt vs. equity and market value behavior - Rana Shahid Imdad Akash; Zaheer Abbas (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2015)
This particular study is regarded to the static trade off theory, pecking order theory, signaling theory and agency theory, life stage theory, transaction cost economics theory, market timing theory. This paper also estimates the results by an interactive structural equation modeling, depends on different theories to associate Debt versus Equity, corporate governance, and value of firm. The relationship of financial structure - Debt versus Equity, corporate governance, and firm value is tried to justify. In this particular study, 70 Non financial listed firms on Equity Market - Karachi Stock Exchange (KSE) are taken. The data is collected for the period of 2006 - 2010. The results presented that corporate governance has significant effect on firm performance under transaction cost economics theory and good corporate governance theory. It is noticeable of the results of corporate governance has significant effect of the value of firm. In addition, it is also shown that does have mediating effect in between the corporate financial structure and firm value. The negative relationship shows an agency problem. Therefore, the investors do not have the equal information's of the particular firm as the manager holds. Furthermore, the financial singling and asymmetries of information's hypothesis reflected that choice of debt or equity should impact the behavior of the investor due to information asymmetries, it is negative to increase threaten of bankruptcy. This research also concludes the basic premise to examine the structure equation modeling of impact of corporate governance and firm performance in the construction of portfolio for best alignment of cost of signaling and asymmetric risk.
Keywords: 330; capital structure; structural equation model; corporate governance; transaction cost economics theory